(untitled) (The Peerian Journal, 2026)
This article considers the methodology for using portfolio technology to assess the lexical competence of future foreign language teachers. The limitations of the traditional summative assessment system are analyzed, and the advantages of portfolio technology as an authentic and process-oriented assessment tool are shown. The study is based on the results of pedagogical observation and experiments conducted with 1st year students of the Namangan State Institute of Foreign Languages named after Is’hoqkhon Ibrat